2009
DOI: 10.2110/palo.2008.p08-129r
|View full text |Cite
|
Sign up to set email alerts
|

A pterosaur manus track from Denali National Park, Alaska Range, Alaska, United States

Abstract: We report on the first record of a pterosaur from Alaska. This record consists of a single manus track from the lower part of the Upper Cretaceous Cantwell Formation in Denali National Park, Alaska, United States, making this the northernmost occurrence for this group of reptiles. The specimen is from deposits that record a low-lying floodplain with small lakes and ponds, dissected by small channels that fed a larger tributary stream on an active fan lobe. The dominant vegetation was comprised of conifers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Many of these trackways, however, are unlike the specimens described by Hitchcock (1858Hitchcock ( , 1865 and can be assigned to other ichnotaxa, or were not figured. For example, Melchor (2004) and Fiorillo et al (2009) did not figure the specimens that they reported; furthermore, Fiorillo et al were uncertain of the ichnogeneric assignment of the trackways. Additionally, Santi (2006) illustrated trackways that were similar to those reported by Demathieu et al (1992) and Durand (2001).…”
Section: Geographic and Stratigraphic Distributionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many of these trackways, however, are unlike the specimens described by Hitchcock (1858Hitchcock ( , 1865 and can be assigned to other ichnotaxa, or were not figured. For example, Melchor (2004) and Fiorillo et al (2009) did not figure the specimens that they reported; furthermore, Fiorillo et al were uncertain of the ichnogeneric assignment of the trackways. Additionally, Santi (2006) illustrated trackways that were similar to those reported by Demathieu et al (1992) and Durand (2001).…”
Section: Geographic and Stratigraphic Distributionmentioning
confidence: 97%
“…Outside of the Hartford and Deerfield basins, tentative occurrences of Bifurculapes have been recorded from the Permian of France and Italy (Demathieu et al 1992;Durand 2001;Santi 2006), the Triassic of Argentina (Melchor 2004), the Jurassic of Utah Milner et al 2009), and the Cretaceous of Alaska (Fiorillo et al 2009). Many of these trackways, however, are unlike the specimens described by Hitchcock (1858Hitchcock ( , 1865 and can be assigned to other ichnotaxa, or were not figured.…”
Section: Geographic and Stratigraphic Distributionmentioning
confidence: 99%
“…C. H. Hitchcock (1889) reported Sagittarius, which is herein considered a junior subjective synonym of Bifurculapes, from Connecticut and New Jersey. Getty (2016) also reviewed the tentative occurrences of Bifurculapes from the Permian of France and Italy (Demathieu et al, 1992;Durand, 2001;Santi, 2006), the Triassic of Argentina (Melchor 2004), the Jurassic of Utah (Lucas et al, 2006;Milner et al, 2009), and the Cretaceous of Alaska (Fiorillo et al, 2009). He concluded that of these, the only specimen that should be included within Bifurculapes based on the information provided in the papers describing them was the one from Utah.…”
Section: Geographic and Stratigraphic Distributionmentioning
confidence: 99%
“…Further, coupled with the Late Cretaceous fossil vertebrate remains found throughout Alaska, this was a widespread and rich terrestrial polar ecosystem (Brouwers et al, 1987;Parrish et al, 1987;Clemens and Nelms, 1993;Gangloff, 1995Gangloff, , 1998Gangloff, 2000, 2001;Fiorillo and Parrish, 2004;Gangloff et al, 2005;Fiorillo et al, 2009aFiorillo et al, ,b, 2011Fiorillo et al, , 2014aGangloff and Fiorillo, 2010;Fiorillo and Adams, 2012;Tykoski, 2012, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…As a result of these surveys, the central Alaska Range, and specifically Denali National Park, is now recognized to record a remarkable Late Cretaceous Arctic terrestrial ecosystem (Fiorillo et al, 2009a(Fiorillo et al, , 2011(Fiorillo et al, , 2014aTomsich et al, 2010Tomsich et al, , 2014Fiorillo and Adams, 2012).…”
Section: Introductionmentioning
confidence: 99%